Community Service for Postpartum Mothers with Perineal Wounds in the Pardamean Community Health Center Work Area - Friani, Sri Rahma; Situngkir, Lidya Sartika; Silitonga, Rumondang (PT Inovasi Pratama Internasional, 2022)
This research is entitled Community Service for Postpartum Mothers with Perineal Wounds in the Pardamean Community Health Center Work Area. The Maternal Mortality Rate (MMR) in Indonesia is still quite high when compared to other ASEAN countries. Data from the Data and Information Center of the Indonesian Ministry of Health in 2007 the maternal mortality rate was 228/100,000 live births, but data in 2012 the MMR in Indonesia increased again to 359/100,000 live births. The main cause of death in maternal cases is a direct cause due to complications of pregnancy, childbirth and postpartum. One of the direct causes during the postpartum period is infection, amounting to 11% to 30% of cases (Fibriana, 2007). The causes of infection during the postpartum period include: midwifery services that are still far from perfect, insufficient maternal immunity, poor postpartum care, malnutrition, anemia, poor hygiene, and fatigue. Prevention related to the risk of infection during the postpartum period due to wounds on the perineum includes: perineal wound care, providing good nutrition, personal hygiene and early mobilization. The partner understands and agrees to perineal care, and is able and willing to perform it effectively. The partner understands, agrees to, and is able to breastfeed effectively. The partner has a good understanding of how to maintain family resilience. The partner has a good understanding of how to meet the family's nutritional needs.